Relationship between Serum Magnesium Status and the Incidence of Preeclampsia at 8 Padang Primary Health Care - Fajriati, Hifzhillah; Utama, Bobby Indra; Nurhayati, Nurhayati (Andalas Obstetrics And Gynecology Journal, 2024)
Introduction: Preeclampsia is one of the main causes of maternal morbidity and mortality, with its etiology and pathophysiology not fully understood. Several studies have shown that magnesium plays an important role in preeclampsia. Magnesium plays a role in modulating endothelial function. Decreased serum magnesium levels in pregnancy can trigger endothelial dysfunction that has an impact on the occurrence of preeclampsia.Objective: Determine the relationship between serum magnesium status with incidence of preeclampsia in pregnant women at 8 Padang Primary Health Care.Method: An observational analytic with cross-sectional design. Sampling was carried out using total sampling technique from research master data at 8 Padang Primary Health Care for period June 2019 – May 2020. The total sample was 45 pregnant women who met the inclusion and exclusion criteria. Data were analyzed using Fisher’s.Result: The serum magnesium status of pregnant women in the 8 Padang Primary Health Care was dominated by normal serum magnesium status (91.1%) and only 8.9% of pregnant women had preeclampsia. Fisher’s test showed that there was a significant relationship between serum magnesium status and the incidence of preeclampsia (p-value = 0,034).Conclusion: There is a significant relationship between serum magnesium status and preeclampsia (with overlook the factors of previous preeclampsia history, family history of preeclampsia, and magnesium intake during pregnancy). Hypomagnesemia status in pregnant women can exacerbate the occurrence of preeclampsia.